Biosensors based on conductometric detection - Soldatkin, A.P.; Dzyadevich, S.V.; Korpan, Y.I.; Arkhipova, V.N.; Zhylyak, G.A.; Piletsky, S.A.; Sergeeva, T.A.; Panasyuk, T.L.; El'skaya, A.V. (Биополимеры и клетка, 1998)
The present paper is a self-review on the development of about 20 conductometric biosensors based on planar electrodes and containing different biological material (enzymes, cells, antibodies), bio-mimics or synthetic membranes, including Imprinting polymers, as a sensitive element. Highly specific, sensitive, simple, fast and cheap determination of different analytes makes them promising for needs of medicine, biotechnology, environmental control, agriculture and food industry. Non-specific interference of back-ground ions may be overcome by the differential mode of measurement, the usage of rather concentrated sample buffer and additional negatively or positively charged membranes, which decrease buffer capacity influence and extend a dynamic range of sensors response. For development of easy-to-use small conductometric immunosensors several approaches seem to be promising: i) the usage of polyaniline as electroconductive label for antibodies detection in competitive electroimmunoassay; ii) the elaboration of multilayer structures with phtalocyanine films; iii) the usage of acrylic copolymeric membranes. The advantages and disadvantages of conductometric biosensors created are discussed. For future commercialisation our effort are aimed to unite a thin-film technology with membranes deposition and to find the ways of membrane stabilisation, including bio-mimics creation, utilisation of bioaffinity polymeric membranes, imprinting polymers etc. Огляд присвячено аналізу власних робіт з розробки близько 20 кондуктометричних біосенсорів на основі планарних електродів та різноманітного біологічного матеріалу (ферменти, клітини, антитіла), синтетичних мембран як чутливих елементів. Висока селективність, чутливість, низька ціна, простота та експресність визначення різноманітних речовин роблять біосенсори необхідними для потреб медицини, біотехнологїі, екологи, сільського господарства та харчової промисловості. При аналізі реальних зразків неспецифічний вплив фонових електролітів можна суттєво зменшити завдяки використанню диференційного режиму вимірювань, більш концентрованих буферних розчинів, а також додаткових негативно чи позитивно заряджених мембран, які запобігають впливові буферної ємності та іонної сили розчинів і розширюють динамічний діапазон роботи сенсорів. Для створення мініатюрних імуносенсорів було запропоновано такі підходи: а) використання поліаніліну як електропровідної мітки при виз наче пні антитіл у конкурентному імуноаналізі: б) створення багатошарових структур з плівками фталоціаніну; в) використання акрилових сополімерних мембран. Обговорено переваги та недоліки розроблених кондуктометричних біосенсорів. Подальша комерціалізація таких приладів пов'язана з пошуком шляхів стабілізації чутливих мембран та суміщення тонкоплівкових технологій з нанесенням мембран у єдиному технологічному циклі. Обзор посвящен анализу собственных работ по разработке около 20 кондуктометрических биосенсоров на. основе планарных электродов и различного биологического материала, (ферменты, клетки, антитела) и синтетических мембран о качестве чувствительных элементов. Высокая селективность, чувствительность, дешевизна, простота и быстрота определения различных веществ делают биосенсоры необходимыми в медицине, биотехнологии, экологии, сельском хозяйстве и пищевой промышленности. При анализе реальных образцов неспецифическое влияние фоновых электролитов можно устранить благодаря использованию дифференциального режима измерений, более концентрированных буферных растворов, а также дополнительных отрицательно или положительно заряженных мембран, уменьшающих влияние буферной емкости и ионной силы растворов и расширяющих динамический диапазон работы сенсоров. Для создания миниатюрных иммуносенсоров предложены следующие подходы: а) использование полианилина как электропроводящей метки при определении антител в конкурентном иммуноанализе; б) создание многослойных структур с пленками на основе фталоцианина; в) использование акриловых со полимерных мембран. Обсуждены преимущества и недостатки разработанных кондуктометрических биосенсоров. Дальнейшая коммерциализация, таких приборов связана с поиском путей стабилизации чувствительных мембран и совмещения, тонкопленочной технологии с нанесением мембран в едином технологическом цикле.